Novel hollow titanium dioxide nanospheres with antimicrobial activity against resistant bacteria - de Dicastillo, Carol López; Patiño, Cristian; Galotto, María José; Vásquez-Martínez, Yesseny; Torrent, Claudia; Alburquenque, Daniela; Pereira, Alejandro; Escrig, Juan (Beilstein Journal of Nanotechnology, 2019)
The search for and synthesis of new antimicrobial nanostructures is important to reduce microbial incidence that induces infectious diseases and to aid in the antibiotic resistance crisis, which are two of the most pressing issues in global public health. In this work, novel, hollow, calcined titanium dioxide nanospheres (CSTiO2) were successfully synthesized for the first time through the combination of electrospinning and atomic layer deposition techniques. Poly(vinylpyrrolidone) (PVP) electrosprayed spherical particles were double-coated with alumina and titanium dioxide, and after a calcination process, hollow nanospheres were obtained with a radius of approximately 345 nm and shell thickness of 17 nm. The structural characterization was performed using electron microscopy, and X-ray diffraction and small-angle X-ray diffraction evidenced an anatase titanium dioxide crystalline structure. Thermogravimetric analysis and Fourier-transform infrared spectroscopy studies demonstrated the absence of polymer residue after the calcination process. The antimicrobial properties of the developed CSTiO2 hollow nanospheres were evaluated against different bacteria, including resistant E. coli and S. aureus strains, and when compared to commercial TiO2 nanoparticles, CSTiO2 nanospheres exhibited superior performance. In addition, the positive effect of UV irradiation on the antimicrobial activity was demonstrated.
Keywords: antimicrobial nanoparticles; atomic layer deposition; electrospinning; hollow nanospheres; titanium dioxide

(untitled) - Dakal, T. C.; Kumar, A.; Majumdar, R. S.; Yadav, V. (Front. Microbiol., 2016)

(untitled) - Wang, L.; Hu, C.; Shao, L. (Int. J. Nanomed., 2017)

(untitled) - Rai, M. K.; Deshmukh, S. D.; Ingle, A. P.; Gade, A. K. (J. Appl. Microbiol., 2012)

(untitled) - Kadiyala, U.; Turali-Emre, E. S.; Bahng, J. H.; Kotov, N. A.; VanEpps, J. S. (Nanoscale, 2018)

(untitled) - Siddiqi, K. S.; ur Rahman, A.; Tajuddin; Husen, A. (Nanoscale Res. Lett., 2018)

(untitled) - Xu, Z.; Zhuang, C.; Zou, Z.; Wang, J.; Xu, X.; Peng, T. (Nano Res., 2017)

(untitled) - Zhao, Z.; Zhang, X.; Zhang, G.; Liu, Z.; Qu, D.; Miao, X.; Feng, P.; Sun, Z. (Nano Res., 2015)

(untitled) - Feng, X.; Pan, F.; Zhao, H.; Deng, W.; Zhang, P.; Zhou, H.-C.; Li, Y. (Appl. Catal., B, 2018)

(untitled) - Qiu, K.; Durham, P. G.; Anselmo, A. C. (Nano Res., 2018)

(untitled) - Li, H.; Zhou, Q.; Gao, Y.; Gui, X.; Yang, L.; Du, M.; Shi, E.; Shi, J.; Cao, A.; Fang, Y. (Nano Res., 2015)

(untitled) - Dhanasekar, M.; Jenefer, V.; Nambiar, R. B.; Babu, S. G.; Selvam, S. P.; Neppolian, B.; Bhat, S. V. (Mater. Res. Bull., 2018)

(untitled) - De Falco, G.; Porta, A.; Del Gaudio, P.; Commodo, M.; Minutolo, P.; D’Anna, A. (MRS Adv., 2017)

(untitled) - Aytekin Aydın, M. T.; Hoşgün, H. L.; Dede, A.; Güven, K. (Spectrochim. Acta, Part A, 2018)

(untitled) - Xu, Z.; Kan, Y.; Liu, C. (Mater. Res. Bull., 2018)

(untitled) - Pat-Espadas, A. M.; Cervantes, F. J. (J. Chem. Technol. Biotechnol., 2018)

(untitled) - Liu, D.; Zhang, C.; Dong, G.; Xu, C.; Liu, D.; Lv, Y.; Zhong, B.; Wang, B. (Mater. Res. Express, 2018)

(untitled) - Liu, X.; Yang, Y.; Yu, D.-G.; Zhu, M.-J.; Zhao, M.; Williams, G. R. (Chem. Eng. J., 2019)

(untitled) - López de Dicastillo, C.; Patiño, C.; Galotto, M.; Palma, J.; Alburquenque, D.; Escrig, J. (Nanomaterials, 2018)

(untitled) - Porro, S.; Bejtka, K.; Jasmin, A.; Fontana, M.; Milano, G.; Chiolerio, A.; Pirri, C. F.; Ricciardi, C. (Nanotechnology, 2018)

(untitled) - Ricci, P. C.; Laidani, N.; Chiriu, D.; Salis, M.; Carbonaro, C. M.; Corpino, R. (Appl. Surf. Sci., 2018)

(untitled) - Cui, L.; Liu, Z.-P.; Yu, D.-G.; Zhang, S.-P.; Bligh, S. W. A.; Zhao, N. (Colloid Polym. Sci., 2014)

(untitled) - Munir, M. M.; Suryamas, A. B.; Iskandar, F.; Okuyama, K. (Polymer, 2009)

(untitled) - Edy, R.; Zhao, Y.; Huang, G. S.; Shi, J. J.; Zhang, J.; Solovev, A. A.; Mei, Y. (Prog. Nat. Sci.: Mater. Int., 2016)

(untitled) - Mallakpour, S.; Behranvand, V. (Prog. Org. Coat., 2015)

(untitled) - Mallakpour, S.; Jarang, N. (Polym. Bull., 2018)

(untitled) - Hulsey, S.; Absar, S.; Sultana, Q. N.; Sabet, S. M.; Mahfuz, H.; Khan, M. (Polym. Compos., 2018)

(untitled) - Kavre Piltaver, I.; Peter, R.; Šarić, I.; Salamon, K.; Jelovica Badovinac, I.; Koshmak, K.; Nannarone, S.; Delač Marion, I.; Petravić, M. (Appl. Surf. Sci., 2017)

(untitled) - Bishal, A. K.; Sukotjo, C.; Takoudis, C. G. (J. Vac. Sci. Technol., A, 2017)

(untitled) - Xiao, Z.; Guo, P.; Sun, N. (J. Appl. Polym. Sci., 2017)

(untitled) - Mangalam, R.; Thamilselvan, M.; Selvasekarapandian, S.; Jayakumar, S.; Manjuladevi, R. (Ionics, 2017)

(untitled) - Saroj, A. L.; Singh, R. K.; Chandra, S. (Mater. Sci. Eng., B, 2013)

(untitled) - Hong, H.-K.; Park, C.-K.; Gong, M.-S. (Bull. Korean Chem. Soc., 2010)

(untitled) - Bai, J.; Li, Y.; Sun, L.; Zhang, C.; Yang, Q. (Bull. Mater. Sci., 2009)

(untitled) - López de Dicastillo, C.; Roa, K.; Garrido, L.; Pereira, A.; Galotto, M. (Polymers (Basel, Switz.), 2017)

(untitled) - Kuchi, C.; Harish, G. S.; Reddy, P. S. (Ceram. Int., 2018)

(untitled) - Subhapriya, S.; Gomathipriya, P. (Microb. Pathog., 2018)

(untitled) - Wang, Z.; Saxena, S. K.; Pischedda, V.; Liermann, H. P.; Zha, C. S. (J. Phys.: Condens. Matter, 2001)

(untitled) - Mendoza-Anaya, D.; Salas, P.; Angeles-Chávez, C.; Pérez-Hernández, R.; Castaño, V. M. (Rev. Mex. Fis., 2004)

(untitled) - Yoganarasimhan, S. R.; Rao, C. N. R. (Trans. Faraday Soc., 1962)

(untitled) - Nagalakshmi, M.; Karthikeyan, C.; Anusuya, N.; Brundha, C.; Basu, M. J.; Karuppuchamy, S. (J. Mater. Sci.: Mater. Electron., 2017)

(untitled) - Purbia, R.; Borah, R.; Paria, S. (Inorg. Chem., 2017)

(untitled) - Shi, W. M.; Dai, X. J.; Yang, G. C.; Xu, Y.; Liu, Y. (Mater. Sci. Forum, 2013)

(untitled) - Esfandiari, N.; Simchi, A.; Bagheri, R. (J. Biomed. Mater. Res., Part A, 2014)

(untitled) - Cushing, B. L.; Kolesnichenko, V. L.; O'Connor, C. J. (Chem. Rev., 2004)

(untitled) - Pessoa, R. S.; dos Santos, V. P.; Cardoso, S. B.; Doria, A. C. O. C.; Figueira, F. R.; Rodrigues, B. V. M.; Testoni, G. E.; Fraga, M. A.; Marciano, F. R.; Lobo, A. O.; Maciel, H. S. (Appl. Surf. Sci., 2017)

(untitled) - Park, J. Y.; Choi, S.-W.; Kim, S. S. (Nanotechnology, 2010)

(untitled) - Baptista, P. V.; McCusker, M. P.; Carvalho, A.; Ferreira, D. A.; Mohan, N. M.; Martins, M.; Fernandes, A. R. (Front. Microbiol., 2018)

(untitled) - Li, Y.; Zhang, W.; Niu, J.; Chen, Y. (ACS Nano, 2012)

(untitled) - Roy, A. S.; Parveen, A.; Koppalkar, A. R.; Ambika Prasad, M. V. N. (J. Biomater. Nanobiotechnol., 2010)

(untitled) - Brunet, L.; Lyon, D. Y.; Hotze, E. M.; Alvarez, P. J. J.; Wiesner, M. R. (Environ. Sci. Technol., 2009)

(untitled) - Fu, G.; Vary, P. S.; Lin, C.-T. (J. Phys. Chem. B, 2005)

Methods for Determining Bactericidal Activity of Antimicrobial Agents - Barry, A. L.; Craig, W. A.; Nadler, H.; Barth Reller, L.; Sanders, C. C.; Swenson, J. M. (1999)